Edmundas Malūkas in the Literary Field: The Trajectory and the Strategies of a Popular Writer - Oral, Taisija (Literatūra, 2025)
The lack of research on popular literature is evident to those interested in contemporary Lithuanian literary processes and their critical interpretation. The number of popular novels is growing every year, and they are becoming more diverse, yet there is still a lack of detailed, conceptual, and consistent research. This article aims to address the question why this is the case and to initiate an empirically based discussion about the emergence of popular literature after the restoration of Lithuanian independence. Based on Pierre Bourdieu’s insights into the structure and patterns of the literary field, a case study is conducted: the trajectory of one of the most popular novelists of the early 1990s, Edmundas Malūkas, in the literary field and the paratextual strategies of his books are analyzed. The aim is to investigate how, on the one hand, the gate-keepers of the subfield of small-scale production and, on the other hand, the media and readers react to the phenomenon of Edmundas Malūkas, and, as a next step, to determine how the writer himself interprets his activity in the literary field, what position he aspires to, and what strategies he implements. Having debuted as an author of genre literature, Malūkas then manifests a different, and arguably a more authentic strategy and pragmatics of literature in his third novel. Despite the rejection of the Writer’s Union, along with the limited and mostly unfavorable reviews by professional critics, Malūkas tries his hand at other literary forms (short stories, autobiographical writing, and historical novels) and strives for stylistic mastery. However, in the process, he moves away from his earlier mass readership without being able to appeal to an elite audience. This analysis of Malūkas’ trajectory and the changes in his strategy allow us to see the field of Lithuanian literature after the restoration of independence from a new perspective, which is grounded in the experience of a writer categorized within popular literature and thus experiencing differently the power effects of the literary field.